Multiple geochemical, mineralogical and isotopic approaches to constrain the deposition conditions of Gazlıgöl travertines, western Turkey. (April 2022) - Mutlu, Halim; Karabacak, Volkan; Deniz, Kıymet; Erkkila, Brad R.
Abstract: Owing to the complex tectono-magmatic evolution within the Alpine-Mediterranean belt, Turkey hosts numerous geothermal springs, which actively precipitate travertine deposits. In this study, we investigate geochemistry, stable and isotopic, mineralogical features, and depositional conditions of fissure-ridge travertines in the Gazlıgöl area, western Anatolia. U/Th age data of the studied travertines, which are precipitated by CO2 -rich waters depressurized during episodic seismic events, vary from 279 ± 82 to 110 ± 61 ka revealing a prolonged seismic activity from middle to late Pleistocene. Gazlıgöl travertines composing chiefly of calcite have δ 18 O values in the range of −18.5 to −16.4‰ (VPDB) and δ 13 C values between 1.8 and 2.4‰ (VPDB). Δ47 values of samples vary from 0.584 to 0.638‰ and crystallization temperatures are estimated in a wide range between 36 ± 6 and 68 ± 4 °C. Considering the oxygen isotope fractionation between calcite and water (Δ 18 OCc-water ), δ 18 O of paleofluids which precipitated the Gazlıgöl travertines was computed in the range of −14.9 to −10.6‰ (VSMOW), which is similar to the isotope composition of modern thermal waters (−13.1 to −10.9‰, VSMOW) of meteoric derivation in the study area. 87 Sr/ 86 Sr values of Gazlıgöl travertines fall in a narrow range from 0.720667 to 0.720837, suggesting that bedrocks in the Gazlıgöl area are the source of Sr in calcite bands. Like other travertines in western Anatolia, REE compositions of Gazlıgöl fissure samples are significantly lower than basement lithologies, which might be attributed to insufficient time for the interaction of CO2 -bearing waters with the host rock because of their rapid ascent. Highlights: U/Th age of Gazlıgöl travertines (279 ± 82 to 110 ± 61 ka) reveal a prolonged seismic activity. Δ47 values of vein samples estimate crystallization temperature between 46 and 68 °C. Homogenization temperatures measured inclusions follow the range of 46–71 °C. Enrichment of 18 O and 13 C in travertines imply precipitation by rapid CO2 degassing.